Application of Rainfall Stochastic Simulation Based on Copula Function in Ancient Yellow River Basin - PAN Qixin; LI Fan; LIU Ping; LI Chunxiu (Renmin Zhujiang)
Taking the monthly rainfall data of the three hydrological stations,namely Suqian Station at the upper reaches,Liulaojian Station at the middle reaches,and Xinyuan Station at the lower reaches of the ancient Yellow River in Suqian City,Jiangsu Province for 39 years (1980—2018) as the example,this paper conducts the stochastic simulation of monthly rainfall based on the Copula function,establishes the joint distribution of monthly rainfall for two of 3 stations,realizes the stochastic simulation of monthly rainfall of the three stations by Gibbs sampling,and verifies the effectiveness of the simulation prediction by comparing the measured and simulated monthly rainfall.The results show that there is a strong correlation between the rainfall in the upper,middle and lower reaches.The two-dimensional Copula function can effectively establish the correlation structure between adjacent stations in the study area,and serve for the stochastic simulation of rainfall in the basin,which provides a reference for its application in other basins.